SUSTAINABLE BUSINESS MODEL – TABUNG HAJI MALAYSIA VERSUS BADAN PENGELOLA KEUANGAN HAJI INDONESIA - Tasya Aspiranti; Abdul Razak Abdul Hadi (UPT Publikasi Ilmiah UNISBA, 2026)
This study examines the sustainability of Hajj fund management by comparing the business models of Lembaga Tabung Haji (TH) Malaysia and Badan Pengelola Keuangan Haji (BPKH) Indonesia. The research addresses the challenge of balancing financial performance, Shariah compliance, governance quality, and sustainability obligations in large-scale Islamic public fund institutions. The study aims to evaluate how differing institutional designs influence long-term sustainability outcomes. A comparative mixed- methods approach is employed, combining financial ratio analysis, diversification measurement using the Herfindahl–Hirschman Index, and qualitative governance–ESG content analysis based on audited reports from 2019–2024. The study analyzes six years of audited financial data (2019–2024), including asset growth, profit distribution rates, liquidity coverage ratios, and portfolio concentration indices, ensuring empirical robustness and cross-institutional comparability. The findings indicate that TH’s integrated business-group model achieves stronger financial returns and diversification, while BPKH’s fiduciary stewardship model demonstrates superior liquidity management and governance transparency. Both institutions show moderate ESG integration, indicating room for improvement. The study contributes to sustainable Islamic finance literature by proposing a composite sustainability perspective and offers policy-relevant insights for improving Hajj fund governance in ASEAN countries.